Development of experimental systems for studying the biology of Nudaurelia capensis ß virus - Walter, Cheryl Tracy (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2005)
After 20 years, Nudaurelia ß virus (NßV) was re-isolated from a population of Nudaurelia capensis larvae exhibiting similar symptoms to those described in 1974 for a tetravirus infection. NßV is a member of the Tetraviridae, a family of positive sense insect RNA viruses that exclusively infect Lepidopteran insects. In addition to NbV, there was evidence that the insects were infected with another small RNA virus. SDS-PAGE and Western analysis revealed two proteins (p56 and p58), that cross-reacted with anti-NbV antibodies. Transmission Electron Microscopy (TEM) analysis showed the presence of particles exhibiting a morphology described for NbV and majority of particles of a diameter of 37 nm. In addition there was a second, minor population of particles with a diameter of 34 nm, which also exhibited the characteristic pitted surface of NßV, raising the possibility of two species of NßV in the N. capensis population. To further investigate this, cDNA corresponding to the 3` end of the replicase gene as well as the entire capsid gene of NbV was synthesized and sequenced. Alignments of the cDNA sequence showed a 99.46 % identity to the published sequence of NbV. Two amino acid substitutions were observed in the capsid coding sequence, one of which was a conservative substitution. Both of these substitutions were found in the b-sandwich domain of the capsid protein. Inspection of the capsid coding sequence showed a second methionine (Met50) at the VCAP amino terminus raising the possibility that p56 might arise from a translation product starting at this site. To investigate this, a full length and truncated capsid coding sequence starting at Met50, were expressed in a baculovirus expression system. VLPs were examined by TEM and Western analysis showed the presence of virus like particles with NßV morphology, but smaller in diameter than the wild-type with an average of 33.33 nm, similar to the smaller particles observed in the virus preparations of NßV. This result supported the hypothesis that NßV translates a smaller coat protein from the second in-frame methionine residue.
Keywords: Imbrasia cytherea; Insects -- Viruses; RNA viruses; DNA